Use of Ex Vivo Normothermic Perfusion for Quality Assessment of Discarded Human Donor Pancreases. Issue 9 (18th May 2015) - Barlow, A. D.; Hamed, M. O.; Mallon, D. H.; Brais, R. J.; Gribble, F. M.; Scott, M. A.; Howat, W. J.; Bradley, J. A.; Bolton, E. M.; Pettigrew, G. J.; Hosgood, S. A.; Nicholson, M. L.; et al.
<x xml:space="preserve">Abstract</x> A significant number of pancreases procured for transplantation are deemed unsuitable due to concerns about graft quality and the associated risk of complications. However, this decision is subjective and some declined grafts may be suitable for transplantation. Ex vivo normothermic perfusion (EVNP) prior to transplantation may allow a more objective assessment of graft quality and reduce discard rates. We report ex vivo normothermic perfusion of human pancreases procured but declined for transplantation, with ABO‐compatible warm oxygenated packed red blood cells for 1–2 h. Five declined human pancreases were assessed using this technique after a median cold ischemia time of 13 h 19 min. One pancreas, with cold ischemia over 30 h, did not appear viable and was excluded. In the remaining pancreases, blood flow and pH were maintained throughout perfusion. Insulin secretion was observed in all four pancreases, but was lowest in an older donation after cardiac death pancreas. Amylase levels were highest in a gland with significant fat infiltration. This is the first study to assess the perfusion, injury, as measured by amylase, and exocrine function of human pancreases using EVNP and demonstrates the feasibility of the approach, although further refinements are required.